Individualism, Structuralism, and Climate Change. Issue 2 (17th February 2022) - Brownstein, Michael; Kelly, Daniel; Madva, Alex
ABSTRACT: Scholars, journalists, and activists working on climate change often distinguish between "individual" and "structural" approaches to decarbonization. The former concern choices individuals can make to reduce their "personal carbon footprint" (e.g. eating less meat). The latter concern changes to institutions, laws, and other social structures. These two approaches are often framed as oppositional, representing a mutually exclusive forced choice between alternative routes to decarbonization. After presenting representative samples of this oppositional framing of individual and structural approaches in environmental communication, we identify four problems with oppositional thinking and propose five ways to conceive of individual and structural reform as symbiotic and interdependent.